Actual pharmacological biotechnological innovations to improve the quality of patient’s life therapeutic and surgical profile - Karnaukh, Ella; Polikov, H.; Zavgorodniy, A. (My University, 2016)
Modern effective drugs which are obtained by using biotechnological genetic engineering methods presented in this article. The main use in surgical and therapeutic clinical practice presents: modern recombinant probiotic generation V Subalin, which was synthesized by Ukrainian scientists for pharmacological treatment of intestinal dysbiosis, recombinant alpha-interferons Roferon-A (alfa-2a) and Altevir (alfa-2b).
Keywords: genetic engineering